Psycho-Pass: Potret Masyarakat Kontrol dalam Kendali Sistem Algoritmik - Mata Hine, Eirens Josua (Retorik: Jurnal Ilmu Humaniora, 2024)
Psycho-Pass is an anime series in the cyberpunk genre that displays a social portrait of modern Japanese society, which offers the utopia of a “perfect social system.” The author uses this anime as a space to reflect critically on discourses and social realities that currently are or will be formed, in an era where everything is connected to algorithmic systems. The author’s findings reveal that the posthuman reality is something that inevitably occurs in people’s bodies, making them increasingly vulnerable to becoming objects of control and surveillance by both companies and the government. People who are not fully aware are trapped in the illusion of freedom and submit themselves to the supervision of the system. Of course, this kind of situation will give rise to resistance from within and without, which potentially constitute (counter)discourses that do not comply with the system. Dialectically, such resistance has a very important role in raising public awareness in facing the modulation of control society (Deleuze) which has adapted to our behavior. Therefore, criticality is needed, even if there is a need for risky disclosure (parrhesia) in carrying out and carrying out counter-monitoring of system regulations that apply in society.